Investment opportunities in Sabah with reference to tourism / Monica Agnes Jock - Jock, Monica Agnes (1995)
Tourism in Sabah is still lagging behind other states in Malaysia although the State is enjoying benefits in term of revenue generated by the industry. With its rich heritage and beauty, Sabah has great tourism potential which has yet to be develop fully.